Hematoma Following Nerve Block of a Branch of Maxillary Nerve: A Case Report - Naomi Ranjan Singh1 , Rini Behera1 , Satabdi Pattnaik1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The nerve block given to obtain anesthesia in maxillary molars and its supporting structures is the posteriorsuperior alveolar nerve (PSAN) block. One of the common complications of the block is extraoral hematomawhich occurs because of the needle penetration to far posteriorly placing it in the vicinity of pterygoidplexus of veins, maxillary artery resulting in probable inadvertent nicking of the vessel causing effusion ofblood into the surrounding soft tissue resulting in swelling and discoloration. This case report describes thiscomplication and its management.